Omalizumab for the reduction of allergic reactions to foods: a narrative review - Ghouri, Hafsa; Habib, Ashna; Nazir, Zainab; Lohana, Nimerta; Akilimali, Aymar (Frontiers in Allergy, 2024)
The frequency of food allergies varies between 2% and 10%, depending on characteristics including age, region, race, and method of diagnosis self-reported by patients or oral food challenges (OFCs). The most common allergies reported are tree nuts (1.2%), milk (1.9%), peanuts (2.2%), and shellfish (1.3%). Omalizumab injection has now been approved by the FDA for the treatment of immunoglobulin E-mediated food allergies in specific adults and children aged one year or older. This medication reduces the risk of allergic reactions (Type I), which can include anaphylaxis, when an individual accidentally encounters one or more food allergens. Omalizumab functions by binding to IgE and altering IgE-mediated pathways, which lessens IgE's capacity to cause allergic reactions. Promising outcomes from clinical trials and case studies include lowered anaphylactic risk and enhanced tolerance to allergens. Omalizumab, however, may have adverse effects; thus, close observation is required. Overall, this review sheds light on the efficacy, safety, and clinical implications of omalizumab, highlighting its potential as a useful intervention for IgE-mediated food allergies.